Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1097/01.lab.0000027835.77351.bf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-α1 Integrin Subunit Antibody on Anti-Thy-1 Glomerulonephritis

Abstract: ␣1␤1 integrin is a potential collagen-binding extracellular matrix receptor that mediates collagen-dependent cell adhesion, proliferation, migration, and collagen matrix assembly and thereby may participate in the wound healing and pathologic scarring observed in some damaged organs. To clarify the role of ␣1␤1 integrin predominantly expressed on the mesangial cell (MC) surface in nephritic glomeruli, we investigated the involvement of MC-␣1␤1 integrin in rat anti-Thy-1 glomerulonephritis (GN) by administering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…In many fibrotic renal diseases, coordinate induction of the synthesis of matrix proteins and integrins (␣1 or ␣5) was observed (2). An antibody to ␣1 decreased mesangial matrix accumulation in a rat model of glomerulonephritis (25). Overexpression of ␣1␤1 in mesangial cells led to reorganization of the extracellular matrix (26).…”
Section: Discussionmentioning
confidence: 99%
“…In many fibrotic renal diseases, coordinate induction of the synthesis of matrix proteins and integrins (␣1 or ␣5) was observed (2). An antibody to ␣1 decreased mesangial matrix accumulation in a rat model of glomerulonephritis (25). Overexpression of ␣1␤1 in mesangial cells led to reorganization of the extracellular matrix (26).…”
Section: Discussionmentioning
confidence: 99%
“…The differences were evaluated with the Stat Mate III software package (ATMS Co., Ltd., Tokyo, Japan). For urinary protein excretion, blood parameters, and BP, statistical significance was evaluated using a t test (8,33). The data for histology and immunohistochemistry were analyzed using the nonparametric Kruskal-Wallis test for multiple comparisons (8).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…To evaluate the level of glomerular staining with each antibody, we performed semiquantitative analysis as follows: 0 ϭ diffuse, very weak, or absent mesangial staining; 1ϩ ϭ 1 to 25% of focally increased mesangial staining; 2ϩ ϭ 25 to 50% of glomerular tuft demonstrating strong mesangial staining; 3ϩ ϭ 50 to 75% of glomerular tuft demonstrating strong mesangial staining; and 4ϩ ϭ Ͼ75% of glomerular tuft stained strongly. For each kidney section, 30 glomeruli were selected at random and evaluated by the same blinded pathologist; the mean value per section was calculated (33).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…TGF-β induces the expression of the collagen-binding integrins α1β1 and α2β1, which mediate collagen remodeling and myofibroblast contraction (Margadant and Sonnenberg 2010). Earlier studies using cardiac fibroblasts (Carver et al 1995), smooth muscle cells (Gotwals et al 1996), stellate cells (Racine-Samson et al 1997), and mesangial cells (Kagami et al 2002) showed that blocking α1 integrin prevents collagen gel contraction. This is somehow controversial considering that α1β1 integrin does not bind with high affinity to fibrillar type I collagen and binds preferentially to the monomeric form (Jokinen et al 2004).…”
Section: Collagen Fiber Alignmentmentioning
confidence: 96%